Why Don't More Indians Do Better in School? The Battle between U.S. Schooling & American Indian/Alaska Native Education - Brayboy, Bryan McKinley Jones and Lomawaima, K. Tsianina (Daedalus, 2018)
American Indian/Alaska Native education – the training for life of children, adolescents, and adults – has been locked in battle for centuries with colonial schooling, which continues to the present day. Settler societies have used schools to “civilize” Indigenous peoples and to train Native peoples in subservience while dispossessing them of land. Schools are the battlegrounds of American Indian education in which epistemologies, ontologies, axiologies, pedagogies, and curricula clash. In the last century, Native nations, communities, parents, and students have fought tenaciously to maintain heritage languages and cultures – their ways of being in the world – through Indigenous education and have demanded radical changes in schools. Contemporary models of how educators are braiding together Indigenous education and Indigenous schooling to better serve Native peoples provide dynamic, productive possibilities for the future.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE2Mi9kYWVkX2FfMDA0OTI